The Impact of Hedonism, Financial Socialization, and Self-Control on the Digital Consumptive Behavior of Housewives in Kupang City - Maria Maria; Hans A. Lao; Intan Feuk (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Digital transformation has changed household consumption patterns, especially among housewives who are now increasingly active in online shopping activities. This phenomenon cannot be separated from the ease of e-commerce access, aggressive promotions, and various digital financial features such as paylater and e-wallets. On the one hand, these advances provide convenience and efficiency, but on the other hand it also encourages the emergence of excessive consumptive behavior. This study aims to analyze the direct influence of hedonism, financial socialization, and self-control on digital consumptive behavior in housewives. The method used is a quantitative approach with survey techniques through online questionnaires. Housewives were selected purposively based on criteria of having experience in online shopping and the use of digital payment methods. The data analysis technique was carried out by multiple linear regression using SPSS software. The results of the study show that hedonism contributes positively to the high tendency of digital consumption, while financial socialization and self-control play a controlling factor that reduces the intensity of consumptive behavior. The implications of these findings not only enrich the study of consumer behavior in the digital age, but also serve as a basis for the development of family financial education strategies that are more contextual and gender-sensitive.